Side-to-side differences in knee laxity and side hop test may predispose an anterior cruciate ligament reinjury in competitive adolescent alpine skiers - Westin, Maria; Mirbach, Lisbeth I.; Harringe, Marita L. (Frontiers in Sports and Active Living, 2022)
Abstract An anterior cruciate ligament (ACL) injury is a common, severe injury in alpine skiing, and reconstruction (ACLR) is frequently performed in competitive alpine skiers younger than 20 years old. To reduce the re-injury rate both intrinsic and extrinsic risk factors should be examined. The aim was to investigate possible intrinsic risk factors for an ACL re-injury in competitive alpine skiers. A cohort of 384 alpine skiers (191 males/ 193 females) from the Swedish ski high schools were prospectively followed during the high school years. The students were clinically examined and physically tested prior to each ski season. In addition, the RAND 36-Item health survey 1.0 (SF-36, Copyright © 1994 Medical Outcome Trust, distributed by RAND Corporation) and injuries were prospectively registered. Thirty-one of the skiers (5 males/ 26 females) had undergone an ACLR before entering the ski high school. This cohort was analyzed with respect to occurrence of, and possible risk factors for an ACL re-injury (including ipsi- and contra-lateral ACL injuries). Skiers who sustained an ACL re-injury were called “ACL re-injury group” and those who did not sustain an ACL re-injury were called “ACL injury group”. Twelve of the 31 students (39%), ten female and two male skiers, age 16.5(SD 0.5), sustained an ACL re-injury during the two first years at the ski high school. Ten of the 12 ACL re-injuries occurred within 10-23 months from the first injury ((m14.8(SD4.7)) and two ACL re-injuries occurred 29 and 47 months, respectively, from the first injury. Eight of the ACL re-injuries were to the ipsi-lateral knee and four to the contra-lateral knee. There were no differences between the groups with respect to muscle flexibility in the lower extremity, Beighton score, one leg hop for distance or square hop test. Side-to-side differences were found with respect to knee joint laxity, >3 mm, measured with KT-1000 arthrometer (p=0.02), and the side hop test (p=0.04). RAND 36-Item health survey did not predict an ACL re-injury. In conclusion, a side-to-side difference in the side hop test and knee joint laxity (KT-1000) may predispose for an ACL re-injury in competitive adolescent alpine skiers.